Synthesis of γ-Sanshool and Hydroxy-γ-sanshool - Xia, Xuanshu; Toy, Patrick H. (Synlett, 2014)
Members of the family of polyunsaturated amide compounds known as the sanshools are found in various Zanthoxylum species such as Sichuan (or Szechuan) peppercorns (huajiao). γ-Sanshool and hydroxy-γ-sanshool have been synthesized from simple building blocks using an alkyne to (E,E)-1,3-diene isomerization reaction to stereoselectively install the (E,E)-2,4-diene group of the key synthetic intermediate (2E,4E,8Z,10E,12E)-tetradecapentaenoic acid, which in turn was converted into both γ-sanshool and hydroxy-γ-sanshool by reaction with the appropriate amines.
Keywords: alkenes; alkynes; isomerization reactions; natural products; Wittig reactions